A methodology for the probabilistic assessment of behaviour factors - Aníbal Costa (2010)
Given the importance that traditional force-based seismic design still currently exhibits, studies addressing issues related to the definition of the behaviour factor values are considered to be of most interest. A probabilistic methodology is proposed for the calibration of the q-factor relating its value with two fundamental parameters, the displacement ductility capacity measured at a relevant location of the structure and the failure probability Pf. The general foundation of this procedure is based on the probabilistic quantification of the seismic action and, by applying a transformation procedure, of the structural seismic demand in terms of displacement ductility. By recalling well established structural reliability procedures and by making use of nonlinear analysis methods, both static and dynamic, a general probabilistic framework, which is able to relate the ductility capacity, the failure probability Pf and the behaviour factor, is defined. In order to illustrate some of the potentialities of the methodology, an application example is presented, addressing the q-factor assessment for a set of regular and irregular reinforced concrete frame structures, enforcing a given Pf and two different ductility levels.